Bimanual examination of the retrieved specimen and regional hypothermia during robot‐assisted radical prostatectomy: a novel technique for reducing positive surgical margin and achieving pelvic cooling. (December 2014) - Jeong, Wooju; Sood, Akshay; Ghani, Khurshid R.; Pucheril, Dan; Sammon, Jesse D.; Gupta, Nilesh S.; Menon, Mani; Peabody, James O.
<x xml:space="preserve">Abstract</x> Objective To describe a novel method of achieving pelvic hypothermia during robot‐assisted radical prostatectomy (RARP) and a modification of technique allowing immediate organ retrieval for intraoperative examination and targeted frozen‐section biopsies. Patients and Methods Intracorporeal cooling and extraction (ICE) consists of a modification of the standard RARP technique with the use of the GelPOINT™ (Applied Medical, Rancho Santa Margarita, CA, USA), a hand access platform, which allows for delivery of ice‐slush and rapid specimen extraction without compromising pneumoperitoneum. Results The ICE technique reproducibly achieves a temperature of 15 °C in the pelvic cavity with no obvious body temperature change. Adopting this technique during RARP, there was an absolute risk reduction by 26.6% in positive surgical margin rate in patients with pT3a disease when compared with similar patients undergoing conventional RARP (P = 0.04). Conclusions The ICE technique eliminates the potential handicap of decreased tactile sensation for oncological margins, especially in the high‐risk patients. This technique allows the surgeon to immediately examine the surgical specimen after resection, and with the aid of frozen‐section pathology determine if further resection is required. A prospective trial is underway in our centre to evaluate the effects of this novel technique on postoperative outcomes.